CRDTs, Coalgebraically - Liittschwager, Nathan; Tsampas, Stylianos; Castello, Jonathan; Kuper, Lindsey (Leibniz International Proceedings in Informatics, LIPIcs, 2023)
We describe ongoing work that models conflict-free replicated data types (CRDTs) from a coalgebraic point of view. CRDTs are data structures designed for replication across multiple physical locations in a distributed system. We show how to model a CRDT at the local replica level using a novel coalgebraic semantics for CRDTs. We believe this is the first step towards presenting a unified theory for specifying and verifying CRDTs and replicated state machines. As a case study, we consider emulation of CRDTs in terms of coalgebra.
CRIS-Team Scopus Importer:2023-10-06
Keywords: Bisimulation; Coalgebra; Concurrency; Distributed Systems